Cave usage and the implications of multiple taphonomic agents on a faunal assemblage - Bountalis, Alexandra Clare (My University, 2013)
The means in which fossil accumulations in the caves of southern Africa have formed is of great importance. One method of accumulation is via the collecting behaviours of a variety of mammalian species. The core of said behaviour is in the use of caves by these species. This project was designed to give insight to the way that animals in the Cradle of Humankind, South Africa are using caves today. The objective of this research is to give a new understanding to the amount that caves are used by various taxa in South African cave systems, with particular regard to taphonomic agents and potential taphonomic agents. This study was accomplished over a 20-month period by setting up motion sensor cameras outside of cave entrances at the Malapa Nature Reserve. Results have shown that animals use caves at high frequencies, crucial to recognize when examining fossil accumulations.
Keywords: Caves.; Taphonomy.; Animals, Fossil.; Cave animals.; Cradle of Humankind World Heritage Site (South Africa)